L-asparaginase production review: bioprocess design and biochemical characteristics - Castro, Daniel (2022)
In the past decades, production of biopharmaceuticals has gained high interest due to its high sensitivity, specificity and lower risk of negative effects to patients. Biopharmaceuticals are mostly therapeutic recombinant proteins produced through biotechnological processes. In this context, L-Asparaginase (L-Asparagine amidohydrolase, L-ASNase (E.C. 3.5.1.1)) is a therapeutic enzyme that has been abundantly studied by researchers due to its antineoplastic properties. As a biopharmaceutical, L-ASNase has been used in the treatment of acute lymphoblastic leukemia (ALL), acute myeloblastic leukemia (AML) and other lymphoid malignancies, in combination with other drugs. Besides its application as a biopharmaceutical, this enzyme is widely used in food processing industries as an acrylamide mitigation agent and as a biosensor for the detection of L-Asparagine in physiological fluids at nano-levels. The great demand for L-ASNase is supplied by recombinant enzymes from Escherichia coli and Erwinia chrysanthemi. However, production processes are associated to low yields and proteins associated to immunogenicity problems, which leads to the search for a better enzyme source. Considering the L-ASNase pharmacological and food importance, this review provides an overview of the current biotechnological developments in L-ASNase production and biochemical characterization aiming to improve the knowledge about its production.